Analisa Setting Over Current Relay Pada Penyulang Banteng Gardu Induk Bukit Siguntang - Mohammad Noer; Yessi Marniati (Jurnal Teknik Elektro, 2019)
Short circuit fault current magnitude is affected by the disorder point distance, the greater distance the smaller the interference point of the fault current in short-circuited. Based on the analysis on the calculation of the value of setting TMS with existing field is still under appropriate conditions, the calculation of the value obtained at the feeders Banteng Tms OCR is 0.11 seconds while the data field is 0.1 seconds, and to the values calculated on the incoming side of the OCR TMS is 0,249 seconds while data in the field by 0.25 seconds. So also for the OCR setting on the incoming side is for the calculation of 952.63 A and for field of 1000 A. However, for the current setting of the OCR obtained at feeders is 609.125 A computed value that is much larger than the results on the field that is equal to 320 A. So it can be concluded that the existing OCR settings cannot be said to be a good setting in the field. Seen from TMS settings and current values, where the value of the setting on the feeder faster than setting the incoming. This is because if an interruption occurs, the feeders will be used to overcome the disorder so that interference can be minimized to the incoming side.